Caracterização da pesca do camarão Macrobrachium amazonicum na comunidade do Porto dos Milagres, Santarém (Pará, Brasil) - LOPES, Antônio Carlos Pereira (Universidade Federal do Oeste do Pará, 2024)
In the city of Santarém, fishing activity involving the artisanal fishery of shrimp M. amazonicum is daily developed, either for subsistence or acquisition of income. The present study has as general objective to characterize the fishing, processing and commercialization of the Amazonian shrimp (Macrobrachium amazonicum) carried out by fishermen of the Port of Miracles market, in Santarém/PA. The same was developed through semi-structured interviews with fishermen from the Port of Miracles and, fieldwork to know how to install the matapis, harvest, separation, as well as the processing of this crustacean and visitation to the points of sale. The shrimp M. amazonicum fishery, carried out by the fishermen of Port of Miracles, occurs through the use of traps known as matapis, which have characteristics different from those traditionally used in other regions of the Amazon. The traps are installed overnight and the shrimp harvest is done the next morning. After harvest occurs the classification and separation of shrimp, small fish and vegetation. The shrimp is benefited, going through the steps of washing, cooking, pre-drying, drying and packaging, being prepared for commercialization, which is done by women. Such an event takes place at local fairs such as the Port of Miracles Market, Cohab Fair and the Old Airport Fair. The Amazon shrimp fishery is of great importance to the fishermen of the region, however, the species does not have any type of regulation that regulates its capture, which may compromise its maintenance as a fishing resource in the region.